Eksplorasi Etnomatematika Pada Gerakan Tari Manuk Dadali Terhadap Konsep Geometri - Sharron Angel Senduk; Louise M. Saija (Jurnal Padegogik, 2023)
Mathematics is a subject that has several main topics such as shapes and sizes with their own difficulties so that they need to be studied in a way that is closer to everyday life. One way that can be done is to link mathematics with culture, for example, is traditional dance. Manuk Dadali  is a traditional dance from West Java that can be used as learning material for students through ethnomathematics-based learning. This research is an exploratory research conducted to analyze and discuss the geometric concepts contained in the Manuk Dadali Dance using an ethnographic approach. The data is collected by observation, documentation and interviews. Based on the research conducted, it was found that geometric elements in Manuk Dadali dance movements and floor patterns, including angular geometry, two-dimensional geometry, and transformation geometry.